Correlation Of Auditory, Intellectually, Repetition (Air) Learning Models on Student Achievement - Rambe, Andina Halimsyah; Aisyah, Siti (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2023)
The purpose of this study was to determine the correlation between the auditory, intellectual, and repetition learning models on the learning achievement of Santri at LPBA (PP Mambaul Ulum Bata-Bata), while the method used was a quantitative research method with analysis using product moment correlation. The results of the research after the manual analysis showed that the r count was 0.676, higher than the r table value of 0.235, so that the r count was in the range of 0.600 to 0.800 with a high interpretation. The conclusion from this study is that auditory, intellectual, and repetition (AIR) learning have a high relationship with the learning achievement of students at the Arabic Language Development Institute (LPBA) in PP. Mambaul Ulum Bata-Bata is accepted because the work